Development of a pandemic-related core set of quality indicators for quality and patient safety in University Hospitals in Germany - Janis Evers; Natalie Altschuck; Claudia Mehl; Lilly Rüthrich; Lorenz Harst; Felix Walther; Oliver Steidle; Arnt Suckow; Ruth Hecker; Jochen Schmitt; Max Geraedts (BMC Health Services Research)
Abstract Background The COVID-19 pandemic entailed a global health crisis, significantly affecting medical service delivery in Germany as well as elsewhere. While intensive care capacities were overloaded by COVID cases, not only elective cases but also non-COVID cases requiring urgent treatment unexpectedly decreased, potentially leading to a deterioration in health outcomes. However, these developments were only uncovered retrospectively. Especially university hospitals, which were meant to take on a central coordinating role, did not have detailed information on expected healthcare utilization, available resources and capacities, and the quality of medical care. The experience of compromised healthcare and a lack of monitoring during the COVID-19 pandemic made it clear that healthcare systems should be better prepared. Therefore, the aim of this work was to develop a set of indicators suited to detect undesirable developments concerning the provision of inpatient healthcare. Material & methods The study employed a literature review, online surveys, expert interviews, and a multistep evaluation process to develop a core set of quality indicators (QIs) suitable for assessing the resilience of university hospitals during pandemics. This initial set of indicators was refined through consultations with a) quality and risk management officials from German university hospitals via an online survey and b) a diverse panel of experts. Results The comprehensive evaluation identified two primary strands: organizational/management indicators (Strand A, 60 indicators) and disease-specific clinical quality and patient safety indicators (Strand B, 20 indicators for critical conditions like stroke, myocardial infarction, and cancer.) Three additional indicators were added after a final expert panel meeting, resulting in a final set of 83 indicators. Discussion and conclusion The developed QIs mark a significant advancement in the operational preparedness of university hospitals for pandemics. The study contributes to quality management in healthcare during pandemics by creating the basis for a structured approach to pandemic preparedness and response. This unique set of QIs within the German context presents an opportunity for establishing quality improvement, underscoring the importance of a robust, adaptable quality management framework as a basis for safeguarding against future health crises.